25-HYDROXYVITAMIN D3 DEFICIENCY IN HEALTHY ADULT MEN ATTENDING ISRA UNIVERSITY HOSPITAL - Kazi, Navaid; Bhurgari, Ali Nawaz; Shah, Ali Akbar; Kazi, Sumayy (Pakistan Journal of Physiology, 2015)
Serum 25-hydroxy cholecalciferol (25-OH-D3) is a marker of both endogenous production and exogenous supply. The objective of the present study was to determine frequency of 25-hydroxyvitamin D3 (25-OH-D3) deficiency in normal healthy males presenting at the Outpatient Department of Isra University. It was a descriptive study conducted at the Departments of Medicine, Isra University Hospital, Hyderabad, Pakistan, from September 2014 to March 2015. Methods: A sample of 180 normal healthy adult male of age 18–50 years was selected. Cases were selected through non-probability consecutive sampling according to predefined inclusion and exclusion criteria. Informed written consent was obtained from the participants. Biochemical analysis of serum 25-OH-D3 was performed on ARCHITECT I 1000TM system. Data were analysed using Statistix 8.1. Continuous variables were presented as mean and standard deviation whereas categorical variables as frequency and percentages. Difference between categories was measured by using Chi-Square test for goodness of fit and a p<0.05 was considered significant. Results: Mean age of the subjects was 37.6±5.7 years. The mean 25-OH-D3 was observed as 24.57±5.57 ηg/dl (CI 23.19–26.39). Normal, insufficiency, and deficiency of 25-OH-D3 were noted in 4.4% (n=8), 6.6% (n=12) and 88.8% (n=160) of the subjects respectively. Vitamin D3 as low as 7.13 ηg/dl were noted. Conclusion: There is high frequency of 25-hydroxyvitamin D3 deficiency in normal healthy male adults.